Fungicide sensitivity of Dothistroma septosporum isolates in the UK. Issue 2 (30th November 2016) - Piotrowska, M. J.; Ennos, R. A.; Riddell, C.; Hoebe, P. N.
Summary: Dothistroma septosporum, a causal agent of Dothistroma needle blight (DNB), is a damaging fungal pathogen of pines that has recently started to affect native Scots pine woodlands in the UK. In addition to silvicultural methods, fungicide spraying of forest nursery stock can help prevent the spread of DNB. However, the effectiveness of modern single‐site fungicides against D. septosporum and the risk of fungicide resistance evolution remain largely unknown. In this project, we aimed to establish sensitivity profiles of D. septosporum to some widely used single‐site fungicide classes in vitro, and to determine whether fungicide resistance is already present, as this could increase the spread of D. septosporum genotypes on planting stock in native woodlands. For this purpose, we compared isolates of D. septosporum, originating from pine stands unexposed to fungicides, with isolates from nursery outbreaks, for sensitivity to a range of commonly applied fungicides. Most of the fungicides we tested were effective in vitro and we observed no significant shifts in sensitivity in forest nurseries. Although further tests in planta are required to confirm effectiveness of single‐site fungicides against D. septosporum, our results suggest that they can be successfully used in DNB control, although appropriate measures to prevent the evolution of fungicide resistance are strongly recommended.